2021
DOI: 10.1002/smtd.202100093
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Energy Harvesting Materials and Devices for Self‐Powered Water Disinfection

Abstract: Contaminated drinking water is one of the main pathogen transmission pathways making waterborne illnesses such as diarrheal diseases and gastroenteritis a huge threat to public health, especially in the areas where sanitation facilities and gird power are inadequate such as rural and disaster hit areas. Self‐powered water disinfection systems are a promising solution in these cases. In this review paper, the authors provide an overview of the new and emerging methods of applying energy harvesting materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 100 publications
0
13
0
Order By: Relevance
“…177 As such, various biological fungicides have This journal is © The Royal Society of Chemistry 2022 been explored as alternatives for water disinfection. 178,179 Among them, natural polyphenols offer unique advantages owing to their high antimicrobial activity, good biocompatibility, tunable physicochemical properties, and low environmental/human toxicity. And various antimicrobial materials based on natural polyphenols have been developed to obtain clean and safe water in recent years.…”
Section: Water Disinfectionmentioning
confidence: 99%
“…177 As such, various biological fungicides have This journal is © The Royal Society of Chemistry 2022 been explored as alternatives for water disinfection. 178,179 Among them, natural polyphenols offer unique advantages owing to their high antimicrobial activity, good biocompatibility, tunable physicochemical properties, and low environmental/human toxicity. And various antimicrobial materials based on natural polyphenols have been developed to obtain clean and safe water in recent years.…”
Section: Water Disinfectionmentioning
confidence: 99%
“…Recently, the triboelectric nanogenerator (TENG) has been considered a suitable device for bioapplications, [6][7][8][9][10][11][12][13] especially for the human body. [9,10,12,[14][15][16][17] There are three main aspects of TENGs that have drawn researchers' attention.…”
Section: Introductionmentioning
confidence: 99%
“…[19] However, since the triboelectric energy harnessed from ambient energy sources including hand rotation, water/wind flow, and wave vibration can only drive the TENG for low-frequency stimuli (≈Hz), the current output is relatively low (<100 µA). [18][19][20] Consequently, recent studies have shown TENG-driven electroporation disinfection methods to be feasible only for small devices (electrode area <1 cm 2 ) with low throughputs (flow rate <10 mL min -1 ). [18,19,21] While the feasibility of such a system for POU disinfection with high throughputs requirement (≈L min -1 ) is still questionable due to the limitation of insufficient output current.…”
Section: Introductionmentioning
confidence: 99%